2022
DOI: 10.1111/acps.13501
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functioning and suicidal behaviours in patients with first‐episode psychosis: A systematic review

Abstract: Introduction Suicidal behaviour is particularly frequent in patients with psychosis. Therefore, prevention is a key objective of mental health policies. The aim of the current work is to systematically review the association between neurocognitive functioning and suicidal behaviour in patients with first‐episode psychosis (FEP). Material and Methods Of the 3051 studies reviewed, only 7 met the inclusion criteria. Documents in English from their earliest date of coverage until January 2022 were searched for in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…The Center for Disease Control and Prevention survey data reported that 14% of high school students seriously considered killing themselves, 6% attempted suicide in the previous year, and 2% required medical attention [ 5 , 6 ]. However, suicidality within the pediatric population has been more often reported in adolescents diagnosed with psychotic disorders, mostly in the presence of positive symptoms, depression, and anxiety disorders [ 7 ]. Very high risk was also found in young patients with bipolar disorder, specifically in bipolar disorder with psychotic symptoms [ 8 ], panic, and conduct and oppositional defiant disorder [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Center for Disease Control and Prevention survey data reported that 14% of high school students seriously considered killing themselves, 6% attempted suicide in the previous year, and 2% required medical attention [ 5 , 6 ]. However, suicidality within the pediatric population has been more often reported in adolescents diagnosed with psychotic disorders, mostly in the presence of positive symptoms, depression, and anxiety disorders [ 7 ]. Very high risk was also found in young patients with bipolar disorder, specifically in bipolar disorder with psychotic symptoms [ 8 ], panic, and conduct and oppositional defiant disorder [ 9 ].…”
Section: Introductionmentioning
confidence: 99%